Landscape, memory, and post-violence in Cambodia - Tyner, James A. 1966- (London Rowman & Littlefield, 2017)
"Explores how the legacy of violence during the Khmer Rouge regime in Cambodia is memorialized. Engaging with war, violence and critical heritage studies, the book looks at the selective production of heritage diminishes opportunities for justice and reconciliation beyond the violence. It should be of particular interest to students and scholars interested in heritage studies, memory, trauma, genocide, dark tourism, and Cambodia".
Dig a hole and bury the past -- Their bones have piled up -- More than I can speak -- Only if pregnant women were killed -- They just kept bombing -- They are murderous thugs.
Includes bibliographical references (pages 199-215) and index.
Keywords: Collective memory -- Cambodia; Memorialization -- Cambodia; Reconciliation -- Social aspects -- Cambodia; Postwar reconstruction -- Social aspects -- Cambodia; Cambodia -- History -- 1975-1979.